1986
DOI: 10.1099/0022-1317-67-11-2305
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence of a Cloned Hepatitis B Virus Genome, Subtype ayr: Comparison with Genomes of the Other Three Subtypes

Abstract: SUMMARYThe entire nucleotide sequence of genomic DNA was determined for hepatitis B virus (HBV) of subtype ayr, which had been derived from the blood of a Japanese asymptomatic carrier. The genome was 3215 nucleotides long, and differed in DNA sequence by 10 ~ from that of subtypes adw or ayw, but by only 2 9/0 from that of subtype adr. Amino acid sequences coded for by the S, C, P and X genes, as well as by the pre-S region, closely resembled those of subtype adr, indicating that the evolution of HBV/ayr from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(89 citation statements)
references
References 49 publications
1
88
0
Order By: Relevance
“…14,15 Consequently, HBV consists of at least 7 different genotypes (A through G). 14,[16][17][18][19][20] Additionally, another 5 HBV genotypes have been isolated from gibbons, 21,22 chimpanzees, 23,24 gorillas, 25 and orangutans. 26 Until recently, these cases represented infected animals kept in zoos or research primate centers, but evidence is now available of HBV infections in wild-born animals.…”
Section: Hbv Genotypesmentioning
confidence: 99%
“…14,15 Consequently, HBV consists of at least 7 different genotypes (A through G). 14,[16][17][18][19][20] Additionally, another 5 HBV genotypes have been isolated from gibbons, 21,22 chimpanzees, 23,24 gorillas, 25 and orangutans. 26 Until recently, these cases represented infected animals kept in zoos or research primate centers, but evidence is now available of HBV infections in wild-born animals.…”
Section: Hbv Genotypesmentioning
confidence: 99%
“…The third group consisted of the eight previously sequenced HBV clones within group C, specifying adw, (1988), E and F the proposed new genomic groups. Sequences of the clones are from: pHBV320, Bichko et aL (1985); pBRHBadr4, Fujiyama et aL (1983); EcoHBVDNA, Galibert et al (1979); pHBV1-1, Kobayashi et al (1984); pYRB259, Okamoto et al (1986); pSK619, Okamoto et al (1987a);pODW282, pHBB1, pJDW233, pNDR260, pYWB796, pPYW310, pAK66 and plWK146, Okamoto et al (1988); pHBV933 and pHBr330, Ono et aL (1983); pRTB299, Sastrosoewignjo et al (1985). belonging to groups A to D, and by 6.6% to 7.7% from each other, they were classified into separate groups (Fig.…”
Section: The Four Hbv Clones In Group B All Derived Frommentioning
confidence: 99%
“…Therefore, INFa/b can activate transcription of genes possessing ISRE/IRE sequence in their promoters or enhancers [6,18,27]. Previous analysis suggested that an ISRE/IRE sequence was present in the enhancer 1/X gene promoter region of HBV genomic DNA [9,25]. The presence of HBV-IRE suggested that interferon might directly regulate HBV transcription and, consequently, HBV replication [24].…”
Section: Introductionmentioning
confidence: 99%